The role of Portuguese democratisation in the Socialist International’s initiatives towards Latin America in the 1970s - Fonseca, A. M. (Rethinking European social democracy and socialism: The history of the centre-left in Northern and Southern Europe in the late 20th century, 2022)
The purpose of this chapter is to analyse the role that the Socialist International (SI) and Western European Socialist and Social-democratic parties had during the Portuguese democratisation process. Simultaneously, we also wish to understand how Iberian democratic transitions impacted on the modus-operandi of the SI in other areas of the world, namely in Latin America. However, it is impossible to analyse the SI’s perspective in this process without focusing on the role that some socialist and social-democratic European parties played during the 1970s. In this case, the Social Democratic Party of Germany (SPD) is particularly relevant. In fact, the SPD was the leading party in support of the Portuguese socialists, something that was part of its strategy of engagement with the democratisation of Southern Europe.